2020
DOI: 10.1093/rb/rbaa040
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of autogenous, allograft and artificial bone substitutes on bone regeneration and immunotoxicity in rat femur defect model

Abstract: Repair and reconstruction of large bone defect were often difficult, and bone substitute materials, including autogenous bone, allogenic bone and artificial bone, were common treatment strategies. The key to elucidate the clinical effect of these bone repair materials was to study their osteogenic capacity and immunotoxicological compatibility. In this paper, the mechanical properties, micro-CT imaging analysis, digital image analysis and histological slice analysis of the three bone grafts were investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Liang et al . [ 203 ] studied the difference of autogenous, allograft and artificial bone substitutes on bone regeneration, and suggested that the allogenic bone graft has relatively poor bone repair ability compared with autogenous and artificial bone substitutes probably due to the immunotoxicological reaction. This implies the immunogenicity of allogenic cells, and thus the necessity of removal of those cells.…”
Section: The Different Sources Of Biomaterials For Tissue Regenerationmentioning
confidence: 99%
“…Liang et al . [ 203 ] studied the difference of autogenous, allograft and artificial bone substitutes on bone regeneration, and suggested that the allogenic bone graft has relatively poor bone repair ability compared with autogenous and artificial bone substitutes probably due to the immunotoxicological reaction. This implies the immunogenicity of allogenic cells, and thus the necessity of removal of those cells.…”
Section: The Different Sources Of Biomaterials For Tissue Regenerationmentioning
confidence: 99%
“…The cell transfer properties and treatment success depend on the physical properties of the bone graft substitute, including porosity, pore size [ 34 ], and pore interconnectivity [ 23 ]. Considering the influence of biomaterials on stem cell interactions, studies of stem cell–scaffold interactions in relation to proliferation and differentiation are essential components in the search for a favorable scaffold [ 35 , 36 ]. Many in vivo studies have investigated stem cell interactions with bone graft substitutes, and the ability to induce bone growth [ 14 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone defects associated with trauma, infection, and tumor are common clinical symptoms in orthopedics, which require frequent surgical intervention. In most treatments, bone substitutes, including autologous, allogeneic, and artificial bones, are usually required. , Although autologous and allogeneic bone grafts possess superior osteoconduction and osteoinduction, the risks of immune rejection, disease transmission, donor site complications, and limited supply hinder their clinical application. , Bone tissue engineering is a prospective approach to induce bone regeneration and repair. However, the introduction of supraphysiological exogenous growth factors, such as bone morphogenic protein-2 (BMP-2), vascular endothelial growth factor (VEGF), and basic fibroblast growth factor (bFGF), may cause adverse effects like ectopic bone formation, vascular leakage, osteoclast activation, and osteolysis. …”
Section: Introductionmentioning
confidence: 99%
“…In most treatments, bone substitutes, including autologous, allogeneic, and artificial bones, are usually required. 1,2 Although autologous and allogeneic bone grafts possess superior osteoconduction and osteoinduction, the risks of immune rejection, disease transmission, donor site complications, and limited supply hinder their clinical application. 3,4 Bone tissue engineering is a prospective approach to induce bone regeneration and repair.…”
Section: ■ Introductionmentioning
confidence: 99%